Enhancing Indigenous Participation in Higher Education Health Courses in Rural Victoria - Kippen, Sandra; Ward, Bernadette; Warren, Lyn (The Australian Journal of Indigenous Education, 2006)
Abstract The poor health status of Australia’s Indigenous people is well-documented, as are the links between health and education. Aboriginal communities recognise the utmost importance of improving educational, physical, social and economic well-being in an environment where disproportionate numbers of Aboriginal students fail to complete secondary schooling. The aim of this paper is to highlight the issues of access, participation, retention and outcomes for Indigenous students wishing to study or currently studying health courses at a tertiary level. This project used a qualitative descriptive approach, conducting in-depth interviews with a number of key stakeholders and students in rural Victoria. Sixteen participants were interviewed, 14 of whom were from the Indigenous community. Participants identified key issues that were linked to the university and broader community environment. Factors in the university environment included lack of Indigenous staff within the mainstream university system, limited support and culturally inappropriate teaching that lead to negative learning experiences and poor motivation to continue with education. In the broader community, the isolating experience of leaving close-knit rural communities and the influence of past experiences on students’ aspirations for tertiary education was highlighted. The importance of community support and liaison with the university and marketing of health courses to the Indigenous communities in the region were key issues that participants identified as needing further attention.